Analisis Perbandingan Konsep Zakat Menurut Imam Syafi’i dan Undang-Undang Nomor 23 Tahun 2011 - Abdul Rohim; Suprihatin . (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2016)
The purpose of this study to determine the position of the concept of zakat according to the thought of Imam Shafi'i and the Zakat Law, Number 23, 2011 in the perspective of Islamic law and positive law as well as to find out the similarities and differences in both. The method used in this study is a research library with a comparative approach. Among the conclusions of this study is the provision of charity is explained by Imam Shafi'i is a legal doctrine as a source for every Muslim who recognize the truth of thought of Imam Shafi'i. According to Zakat Law No. 23 of 2011, in accordance with article 1, paragraph 2, zakat is a treasure that must be issued by a person or business entity to be given to those who deserve it in accordance shari'ah. Article 4, paragraph 1 is zakat includes zakat mal and zakat fitrah. Various tithes according to Imam Shafi'i thought but there are additions in the Law No. 23 of 2011 concerning the management of zakat is profession zakat or income and services zakat.